2013
DOI: 10.4014/jmb.1209.09038
|View full text |Cite
|
Sign up to set email alerts
|

Panosialins, Inhibitors of Enoyl-ACP Reductase from Streptomyces sp. AN1761

Abstract: In the continued search for inhibitors of enoyl-acyl carrier protein (ACP) reductase, we found that four acylbenzenediol sulfate metabolites from Streptomyces sp. AN1761 potently inhibited bacterial enoyl-ACP reductases of Staphylococcus aureus, Streptococcus pneumoniae, and Mycobacterium tuberculosis. Their structures were identified as panosialins A, B, wA, and wB by MS and NMR data. They showed stronger inhibition against S. aureus FabI and S. pneumoniae FabK with IC50 of 3-5 microM than M. tuberculosis Inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In 2013, the same team isolated four acyl-benzenediol sulphate metabolites, panosialins A , B , wA and wB ( Figure 41 ), from Streptomyces sp. AN1761 [ 170 ]. These four molecules were active against Sa FabI and Sp FabK with IC 50 values in the range of 1.3–5.5 µM.…”
Section: Fas-ii Enzymes and Their Corresponding Inhibitorsmentioning
confidence: 99%
“…In 2013, the same team isolated four acyl-benzenediol sulphate metabolites, panosialins A , B , wA and wB ( Figure 41 ), from Streptomyces sp. AN1761 [ 170 ]. These four molecules were active against Sa FabI and Sp FabK with IC 50 values in the range of 1.3–5.5 µM.…”
Section: Fas-ii Enzymes and Their Corresponding Inhibitorsmentioning
confidence: 99%
“…Research on algal lipids found that loliolide, a ubiquitous monoterpenoid lactone isolated from C. tomentosum, may be used as a neuroprotective agent (Silva et al 2021). The properties of oleamide, an amide derived from the fatty acid oleic acid of Codium, have been reviewed (Kwon et al 2001;Moon et al 2018b). Chemical structure of lipid derivated compounds from Codium species is shown in Fig.…”
Section: Bioactivitiesmentioning
confidence: 99%